Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide